Beta-Thalassaemia Intermedia: Evaluation of Endocrine and Bone Complications. (7th July 2014) - Baldini, M.; Marcon, A.; Cassin, R.; Ulivieri, F. M.; Spinelli, D.; Cappellini, M. D.; Graziadei, G.
Abstract : Objective . Data about endocrine and bone disease in nontransfusion-dependent thalassaemia (NTDT) is scanty. The aim of our study was to evaluate these complications in β -TI adult patients. Methods . We studied retrospectively 70 β -TI patients with mean followup of 20 years. Data recorded included age, gender, haemoglobin and ferritin levels, biochemical and endocrine tests, liver iron concentration (LIC) from T 2 *, transfusion regimen, iron chelation, hydroxyurea, splenectomy, and bone mineralization by dual X-ray absorptiometry. Results . Thirty-seven (53%) males and 33 (47%) females were studied, with mean age 41 ± 12 years, mean haemoglobin 9.2 ± 1.5  g/dL, median ferritin 537 (range 14–4893), and mean LIC 7.6 ± 6.4  mg Fe/g dw. Thirty-three patients (47%) had been transfused, occasionally (24/33; 73%) or regularly (9/33; 27%); 37/70 (53%) had never been transfused; 34/70 patients had been splenectomized (49%); 39 (56%) were on chelation therapy; and 11 (16%) were on hydroxyurea. Endocrinopathies were found in 15 patients (21%): 10 hypothyroidism, 3 hypogonadism, 2 impaired glucose tolerance (IGT), and one diabetes. Bone disease was observed in 53/70 (76%) patients, osteoporosis in 26/53 (49%), and osteopenia in 27/53 (51%). Discussion and Conclusions . Bone disease was found in most patients in our study, while endocrinopathies were highly uncommon, especially hypogonadism. We speculate that low iron burden may protect against endocrinopathy development.